(untitled) (Annals of Medical Research, 2021)
Aim: The prognostic role of lactate for early mortality in patients with ST-segment elevation myocardial infarction (STEMI) submitted to primary percutaneous transluminal coronary angiography (PTCA) is not elucidated clearly. This study was conducted with patients that presented to the emergency department (ED) with STEMI and underwent PTCA to investigate whether the changes in lactate values from ED admission to 24 hours after PTCA affected mortality.Material and Methods: This prospective observational study on 143 patients with STEMI was conducted at emergency service and tertiary-level cardiology clinic in a public university hospital. The documentation for each patient included detailed information on demographics, type of myocardial infarction according to electrocardiography and PTCA results, duration of hospital stay, vital signs, laboratory findings on admission, lactate levels 24 hours after PTCA, and outcome (hospital discharge or death). Results: The lactate values are higher in non-surviving groups measured 24 hours after PTCA (P 0.001). The differences in the lactate levels from the time of admission to 24 hours after PTCA were significantly lower in the non-surviving group (P 0.001). Conclusion: Among patients presenting to the ED with STEMI, a high lactate level is associated with mortality. Also, the difference between lactate values of the patients after PTCA is associated with the risk of mortality. Therefore, we consider that first lactate levels in ED and last lactate levels after PTCA in patients with STEMI can provide physicians with an insight into the possibility of mortality.